Creatine supplementation improves repeated vertical jump performance of volleyball players - Sax, J.; Cummins, R. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Ingestion of creatine monohydrate has sometimes been found to enhance the performance of brief intermittent exercise and when it does the extent of improvement has been in the range of 5-7% (Greenhaff, 1995). The aim of this study was to investigate whether oral creatine supplementation could enhance the ability of volleyball players to perform repeated vertical jumps (three sets of five repetitions) by improving their ability to sustain near maximum jump height. Between repetitions subjects were allowed only sufficient time to regain their balance. Between sets there was a rest interval of 20 seconds. The jumps performed were modified block jumps. Blocking is a facet of volleyball, which requires the player to jump as high as possible with both arms fully extended in order to deflect the ball back into the opposition`s court space. In this study, subjects dipped the second digit of their dominant hand in chalk and 'blocked' against a wall to record the height of their jump. Subjects (19 experienced male volleyball players with a mean age of 25 years) were randomly assigned into either the creatine group (n=9) or the placebo group (n=10). A double blind, pre and post experimental design was used. Subjects were supplemented with either 5g of creatine monohydrate mixed with 5 g of glucose (creatine group) or 10g of glucose (placebo group), taken four times daily for six days.